Effects of physical therapy agents on pain, disability, quality of life, and lumbar paravertebral muscle stiffness via elastography in patients with chronic low back pain. - Yurdakul, Ozan Volkan; Beydoğan, Engin; Yılmaz Yalçınkaya, Ebru (My University, 2019)
This study aims to evaluate early effects of combined hot pack (HP) and transcutaneous electrical nerve stimulation (TENS) treatment and therapeutic ultrasound (US) on pain, quality of life, disability, and the multifidus muscle stiffness.

Between December 2016 and March 2017, a total of 69 patients (36 females, 33 males; mean age 48.9±10.9; range, 27 to 73 years) were included in this randomized-controlled study. The patients were divided into three groups as HT + TENS (Group H+T, n=23), HP + TENS + US (Group H+T+U, n=23), and controls (control group, n=23). All patients filled out the Numeric Rating Scale (NRS), Oswestry Disability Index (ODI), and Short Form-36 (SF-36) questionnaire at baseline and at the end of treatment. The left multifidus muscle strain ratio at fourth lumbar spinal level was obtained from the upper, middle, and lower parts of the muscle along the longitudinal axis on the first and last days of treatment.

There was a significant improvement in the NRS, ODI, and SF-36 physical function, physical role function, pain, and general health perceptions in the H+T and H+T+U groups, compared to the control group (p<0.05). However, there was no significant difference between the H+T and H+T+U groups. The H+T+U group showed an improvement in the SF-36 social role function and emotional role function. There was no significant difference in the multifidus muscle strain ratios among the groups.

Our study results suggest that H+T treatment has a beneficial effect on pain, disability, and certain subscales of the quality of life. However, US seems not to have an additional benefit.
Keywords: Chronic low back pain; elastography; multifidus; physical therapy; ultrasound